Pengaruh Modal Intelektual dan Karakteristik Dewan Pengawas Syariah terhadap Maqashid Syariah Index pada Bank Umum Syariah - Avitariani, Annisa Nurul; Mai, Muhamad Umar; Setiawan; Noeridha, Noorsyah Adi (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
There are strategic issues from the results of the Islamic banking transformation study related to the not optimal quality and quantity of human resources, then the absence of product differentiation, even though the purpose of sharia (maqashid sharia) is the main foundation that needs to be owned by Islamic banking. This study analyzes the effect of intellectual capital (resource measurement) and SSB characteristics on maqashid syariah index. The method used is dynamic panel data regression analysis with first-difference GMM and STATA 17 as a tool. This research results in a significant positive effect between MSIit-t and human capital on MSIit, then capital employed has a significant negative effect on MSIit, and structural capital, SSB education and SSB meetings have no effect on MSIit.